Perancangan Sistem Mobile Reporting Berbasis Android untuk Pelaporan Preventive dan Corrective Maintenance di PT Telkom Indonesia Divisi Regional V - Andre Saputra, Nova; Hari, Yulius; Darmanto, Darmanto (Journal Software, Hardware and Information Technology, 2025)
Preventive, corrective, and maintenance activities are crucial tasks in the NE & OM Division of PT Telkom Indonesia Regional V. Despite the availability of a reporting system through Telegram bot and PACMAN-NEO web, the recording and reporting process is still considered less than optimal and is often complained about at the regional level. The main problems include data inaccuracy, lack of innovation and credibility, and visualization that has not met user expectations. This research aims to overcome the problems of slow, inaccurate, and less real-time reporting, as well as improve the features of navigation, verification, and monitoring of technician activities. The development method used is the System Development Life Cycle (SDLC) Waterfall model. The application was developed using Dart and Flutter as front-end frameworks, PHP and Laravel for API management, and PostgreSQL as the database. The black box test results show that all features function according to user needs. This application has been tested by 3 regional managers, 4 witel managers, 1 regional admin, and 10 technicians. User evaluation showed results of 75% for usability, 63% for ease of use, and 78% for user satisfaction. These results indicate that the developed application is feasible to use as a replacement for the previous Telegram-based PACMAN-NEO system.